Disordered epitopes as peptide vaccines. Issue 3 (14th April 2018) - MacRaild, Christopher A.; Seow, Jeffrey; Das, Sreedam C.; Norton, Raymond S.
Abstract: The development of clinically useful peptide‐based vaccines remains a long‐standing goal. This review highlights that intrinsically disordered protein antigens, which lack an ordered three‐dimensional structure, represent excellent starting points for the development of such vaccines. Disordered proteins represent an important class of antigen in a wide range of human pathogens, and, contrary to widespread belief, they are frequently targets of protective antibody responses. Importantly, disordered epitopes appear invariably to be linear epitopes, rendering them ideally suited to incorporation into a peptide vaccine. Nonetheless, the conformational properties of disordered antigens, and hence their recognition by antibodies, frequently depend on the interactions they make and the context in which they are presented to the immune system. These effects must be considered in the design of an effective vaccine. Here we discuss these issues and propose design principles that may facilitate the development of peptide vaccines targeting disordered antigens. Abstract :